The Prevalence of «Using» Potentially Addictive Objects And Their Addictive Potential Among Patients with Psychopathological Consequences of Traumatic Brain Injury - VoloshynaD. М. (Psychiatry, Neurology and Medical Psychology, 2015)
The purpose of the research is studying the addictive status of patients with various consequences of brain injury using tests with the assessment of prevalence of using potentially addictive objects and their addictive potential in the comparison groups. As a result of a comprehensive assessment of the additive status of patients with psychopathological consequences of traumatic brain injury with the help of AUDIT-these tests more severe tendency of patients with psychopathological consequences of TBI in the formation ofstate dependence in comparison to healthy individuals in the control group was found. The signifi cantly higher addictive potential of some common addictive objects were detected, namely tobacco, Internet, tea and coff ee making facilities, television and computer games.